Transformative Advances in Continuous Glucose Monitoring and the Impact of FDA Over‐the‐Counter Approval on Diabetes Care - Zain Afridi; Sameer Abdul Rauf; Syed Muhammad Nabil Ashraf; Md Ariful Haque (Health Science Reports)
ABSTRACT Introduction Continuous glucose monitoring (CGM) has significantly advanced diabetes management, evolving from early glucose testing methods to modern, FDA‐approved systems. Despite its benefits, challenges related to data security, affordability, and awareness of CGM devices remain. Aim This article explores the historical development, current advancements, and ongoing challenges of CGM systems in diabetes management. It aims to provide insights into how these technologies have transformed patient care and highlight areas needing further improvement. Methods A comprehensive literature review was conducted, focusing on advancements in CGM technology. Sources included PubMed, Google Scholar, and recent guidelines and reviews on CGM systems and their impact on diabetes management. Results The evolution from the Dextrostix test strip to modern CGM systems, including over‐the‐counter devices, has enhanced glucose monitoring and patient outcomes. Recent innovations, such as machine learning models for predicting glucose fluctuations, promise to improve diabetes management. However, issues like data security and device accessibility persist. Conclusion To maximize the benefits of CGM systems, addressing data security, improving affordability, and increasing awareness of CGM devices are crucial. Continued advancements in CGM technology and supportive policies are essential for enhancing diabetes care and patient outcomes globally.